Legal Reform of Diploma Detention in Indonesian Industrial Relations: Balancing Contractual Freedom and Fundamental Rights - Sugeng Santoso PN; Alivia Hasnanda Sakina Maheswari; Soeryaniati Koesoemo; Sri Humana Lagustiani; Kartono Kartono; Sri Hastuti; Andari Yurikosari; Unggul Prayudho Satriyo (Unissula, 2026)
The practice of employers withholding workers’ educational diplomas has emerged as a significant labour law issue in Indonesia due to the absence of explicit statutory regulation governing the practice. This study examines the regulatory vacuum, its implications for workers’ fundamental rights, and the consistency of judicial responses to disputes concerning diploma detention. Using normative legal research with statutory and case approaches, the study analyses relevant legislation and 29 Indonesian court decisions involving civil and industrial relations disputes. The findings reveal that the current legal framework fails to provide adequate legal certainty, resulting in inconsistent judicial decisions. While many courts classify diploma detention as an unlawful act and prioritise substantive justice and worker protection, others rely on procedural formalities or contractual freedom to reject workers’ claims. The recent Minister of Manpower Circular Letter prohibiting diploma detention represents an important policy development but lacks the binding authority of statutory law. This study recommends amending the Manpower Law to explicitly prohibit diploma detention and introduce enforceable administrative and criminal sanctions in order to strengthen legal certainty, judicial consistency, and the protection of workers’ fundamental rights.